0338 Association of Evening Circadian Preference and Languid/Flexible Circadian Type with Predisposing, Perpetuating Factors, and Treatment Acceptability in Patients with Chronic Insomnia Disorder. (25th May 2022) - Singh, Rupsha; Lenker, Kristina; Calhoun, Susan; Fernandez-Mendoza, Julio
Abstract: Introduction: Circadian factors may contribute to sleep difficulties among chronic insomnia disorder (CID) patients who do not otherwise meet full criteria for a circadian rhythm sleep-wake disorder, particularly delayed and advanced sleep-wake phase disorders. Current nosology suggests that using circadian preference measures can provide important diagnostic information and aid in differential diagnosis. However, there is a lack of research identifying clinical factors associated with circadian dimensions in patients with CID. Methods: 195 patients (45.50±15.99 years old, 66.2% female, 15.9% minority) with a diagnosis of CID and absent of any other sleep disorder were evaluated at the Behavioral Sleep Medicine (BSM) program of Penn State Health Sleep Research & Treatment Center. All patients completed measures of circadian preference and type, insomnia severity, arousability, sleep reactivity, pre-sleep arousal, sleep-wake schedule and incompatible behaviors, dysfunctional beliefs and attitudes, mood and stress, and insomnia treatment acceptability. Multivariable linear regression examined which predisposing, perpetuating and treatment acceptability factors were associated with each circadian dimension, while adjusting for age, sex, race/ethnicity and insomnia severity. Results: About 30% of the sample was classified as evening, 29% as morning, 74% as languid, and 43% as flexible types. Sleep-wake irregularity was associated with eveningness (β=-0.276, p<0.01), languidity (β=0.280, p<0.01) and flexibility (β=0.184, p<0.01). Pre-sleep cognitive arousal (β=-0.182, p<0.01) and sleep expectations (β=-0.127, p<0.05) were associated with eveningness. Negative cognitions about the consequences of insomnia (β=0.230, p<0.01) and sleep expectations (β=0.268, p<0.01) were associated with languidity. Sleep-incompatible behaviors (β=0.165, p<0.05) and perceived stress (β=0.267, p<0.01) were associated with flexibility, while trait anxiety (β=-0.137, p=0.058) and negative cognitions about the consequences of insomnia (β=-0.318, p<0.01) were associated with rigidity. Less agreeability to pharmacotherapy over behavioral therapy was associated with morningness (β=0.129, p<0.05), while greater agreeability to behavioral therapy over pharmacotherapy (β=-0.158, p<0.05) was associated with rigidity. Conclusion: Sleep-wake irregularity in patients with CID is a perpetuating factor strongly associated with evening and languid/flexible circadian types, while other predisposing and perpetuating factors can be also determined by circadian preference and/or type. Circadian measures in the evaluation of CID patients may help clinicians individualize BSM treatments, including patients' acceptability. Support (If Any):